(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper enhanced the AODV routing protocol for the prevention of black hole attack. The enhanced AODV routing protocol based on the principle of thresholding. The thresholding using the concept of reference node selection process. The reference node selection process creates two group of node one is path altered group and other is stable path with sensibility. The sensibility path estimates the hop count and packet sequence number. If the number of hop count is not changed or the sequence of packet is also not lost is called sensitivity path of network. The function of threshold generated by the node distance formula based on the Euclidean distance derivation. The enhanced AODV protocol simulate in NS2.34 simulators and measure some standard parameter such as PDR, throughput, overload and E2E delivery ratio.